A method for preparing a high temperature resistant fireproof cable
By using a fire-resistant inner layer composed of expanded graphite and silane materials in the cable, combined with polyvinyl chloride rinse and insulating materials, the problem of poor fire resistance in existing cables in high temperature environments is solved, and higher fire resistance and service life are achieved.
Patent Information
- Application Number
- CN202510187736.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The existing cables have poor fire resistance in high temperature environments, resulting in a rapid reduction in life and it is difficult to effectively utilize the characteristics of expanded graphite to enhance fire resistance.
The preparation method of conductive copper wire and fire-resistant inner layer consisting of expanded graphite, end-hydroxyl polydimethylsiloxane, quartz powder and other materials, and wrapped in insulating materials and polyvinyl chloride outer skin, is used to improve the fire-resistant performance of the cable through the stability of the thermal insulation layer of expanded graphite and the silane-based materials.
Effectively prevent temperature propagation in high-temperature environments, enhance the fire resistance of the cable, improve the stability and durability of the fireproof inner layer, and extend the service life of the cable.
Smart Images

Figure CN119673574B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, and in particular to a method for preparing a high-temperature resistant and fireproof cable. Background Art
[0002] In order to ensure the security of data, people hope that after a fire occurs, there will be enough time to retrieve all data before the entire network is paralyzed, and transfer them to a safe place to minimize the possibility of data loss. Therefore, in the cable standards, there is also a type of fire protection standard, called the "line integrity" standard. Its goal is to keep the cable line unobstructed in the fire scene, so that power and information can still be transmitted normally. Therefore, cables that meet the series integrity requirements are also called fireproof cables;
[0003] Common cables have poor fire resistance during use, which causes their service life to decrease rapidly in high temperature environments, affecting their use effect. It is also inconvenient to utilize the characteristics of expanded graphite to increase fire resistance, resulting in low flexibility in resource utilization. Therefore, we propose a method for preparing high temperature resistant and fireproof cables. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a high temperature resistant and fireproof cable.
[0005] In order to solve the problems raised in the above background technology, the present invention provides the following technical solutions: a method for preparing a high temperature resistant fireproof cable, comprising a conductive copper wire, a fireproof inner layer wrapped by the outer wall of the conductive copper wire, an insulating material, and a polyvinyl chloride outer layer wrapped by the outer wall of the fireproof inner layer, wherein the fireproof inner layer is prepared by weight of expanded graphite, terminal hydroxyl polydimethylsiloxane, quartz powder, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate, and the specific steps of the method for preparing a high temperature resistant fireproof cable are as follows;
[0006] S100, grinding the expanded graphite into powder to prepare powdered expanded graphite, and then filtering the powdered expanded graphite with a filter to obtain finished powdered expanded graphite;
[0007] S200, mixing the finished powdered expanded graphite with quartz powder, and stirring them evenly to obtain a graphite quartz powder mixture;
[0008] S300, adding hydroxy-terminated polydimethylsiloxane, a mixture of graphite quartz powder, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate into a reaction kettle, and stirring them evenly to obtain an initial graphite mixture material;
[0009] S400, transferring the initial graphite mixture material into a vacuum tank, and performing a defoaming treatment on the initial graphite mixture material to obtain a graphite oxane mixture;
[0010] S500, then placing the graphoxane mixture into a coating tank, allowing the conductive copper wire to pass through the graphoxane mixture in the coating tank, so that the outer wall of the conductive copper wire adheres to the graphoxane mixture;
[0011] S600, after the conductive copper wire is adhered to the graphene mixture, removing the excess graphene mixture on the conductive copper wire to obtain a primary treated graphite copper wire, and then placing the primary treated graphite copper wire in an oven to obtain a secondary treated graphite copper wire;
[0012] S700, evenly wrap the insulating material on the secondary treated graphite copper wire to form an insulating layer, and perform quality control on the insulating layer. Finally, evenly wrap the polyvinyl chloride sheath on the outside of the insulating layer of the cable to form a sheath layer, obtain a finished fireproof cable, and perform finished product inspection on the finished fireproof cable.
[0013] As a further solution of the present invention: in S100, the expanded graphite is placed on a grinding device, and the ambient temperature during grinding is controlled between 20°C and 25°C, and then the expanded graphite is ground, and then the powdered expanded graphite is filtered using a filter screen with a mesh size of 300-350 meshes, thereby removing impurities in the powdered expanded graphite, and the quartz powder is ground using the above method, and the quartz powder is filtered using a filter screen with a mesh size of 300-350 meshes.
[0014] As a further solution of the present invention: in the S200, the finished powdered expanded graphite and quartz powder are placed in an oven to remove moisture, the oven temperature range is 90°C-110°C, and the drying time is 5 hours-6 hours, then the finished powdered expanded graphite and quartz powder are taken out, and the finished powdered expanded graphite and quartz powder are placed in a mixing tank according to a weight ratio of 1:2, and the alkalinity environment in the mixing tank is controlled so that the pH value in the mixing tank is between 6 and 8, and the mixing tank is started to mix the finished powdered expanded graphite and the quartz powder at a stirring speed of 50-100 r / min and a stirring time of 20min-40min.
[0015] As a further scheme of the present invention: in the S300, the temperature in the reactor is controlled between 30°C and 50°C, and terminal hydroxyl polydimethylsiloxane, graphite quartz powder mixture, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate are placed in the reactor in order and weight ratio, with a weight ratio of 4:3:1.5:1:0.3:0.2, the reactor is started, and the items inside are stirred at a stirring speed of 100-500r / min and a stirring time of 60min-180min.
[0016] As a further solution of the present invention: in S400, after the initial graphite mixture material is transferred to the interior of the vacuum tank, the vacuum degree of the vacuum tank is adjusted to be between 2000Pa-1400Pa, and the temperature in the vacuum tank is controlled to be between 40°C-45°C, and the working time of the vacuum tank is controlled to be between 50min-60min, and then the initial graphite mixture material is defoamed.
[0017] As a further solution of the present invention: in S500, after the graphoxane mixture is placed inside the coating tank, the temperature of the coating tank is controlled to be between 5°C and 20°C, the humidity is between 40% and 60%, and the effective length of the coating tank is 1m-1.5m, and then the conductive copper wire is inserted into the interior of the graphoxane mixture, and the conductive copper wire is moved inside the graphoxane mixture at a speed between 0.25m / s and 0.5m / s, so that the graphoxane mixture adheres to the conductive copper wire.
[0018] As a further solution of the present invention: in the S600, after the conductive copper wire adheres to the graphoxane mixture, a mixture scraping plate is installed at one end of the coating tank from which the conductive copper wire is led out, and a scraping hole is opened on the mixture scraping plate, and the conductive copper wire adhered to the graphoxane mixture is passed through the scraping hole of the mixture scraping plate to scrape off excess graphoxane mixture, and the graphoxane mixture retained on the conductive copper wire is specifically controlled by the size of the scraping hole and the radius of the conductive copper wire, and the conductive copper wire adhered to the graphoxane mixture is passed through the middle of the scraping hole.
[0019] As a further solution of the present invention: in the S600, a collecting box is installed below the mixture scraping hole, and the temperature in the collecting box is maintained between 5°C and 20°C, so that the scraped graphoxane mixture remains in the same state as the graphoxane mixture in the coating tank, and then the scraped conductive copper wire is transferred to an oven for curing treatment, the temperature in the oven is controlled between 50°C and 80°C, and the working time of the oven is between 100min and 500min.
[0020] As a further solution of the present invention: in the S600, an arc heating rack is installed at the upper end of the mixture scraping plate, the arc heating rack is arranged around the conductive copper wire, and the graphoxane mixture on the conductive copper wire is preliminarily cured by the arc heating rack. The heating temperature of the arc heating rack is between 50°C and 60°C, and a dripping port is opened below the arc heating rack, and the scraped graphoxane mixture enters the collection box through the dripping port.
[0021] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:
[0022] 1. The present invention can form a heat insulation layer by expanding the expanded graphite at high temperature, and the content of the expanded graphite is relatively small. After expansion, it will not damage the insulating material and the polyvinyl chloride outer skin, and can effectively prevent the temperature from propagating, further enhancing the fireproof ability of the cable. Dibutyltin dilaurate can promote the reaction between the components, making the performance of the fireproof inner layer more stable, and using silane materials such as terminal hydroxyl polydimethylsiloxane, methyltriethoxysilane, and γ-aminopropyltriethoxysilane, the stability and durability of the fireproof inner layer can be improved;
[0023] 2. The present invention performs similar grinding on quartz powder to make it similar to the mesh number of finished powdered expanded graphite, so that the two materials can be more evenly combined, and the overall performance of the fireproof inner layer is improved. The finished powdered expanded graphite and quartz powder are placed in an oven to remove moisture, thereby increasing the dryness of the two materials and enhancing the bonding force between them, which is also helpful to improve the insulation performance of the cable. Sufficient stirring is also helpful to the interaction between the components, improving the overall performance of the fireproof inner layer, and can effectively remove bubbles in the initial graphite mixture, so that the fireproof inner layer is more compact.
[0024] 3. The present invention can maintain good fluidity and stability by controlling the temperature of the coating tank, so that the conductive copper wire can evenly adhere to the mixture, and can ensure that the conductive copper wire has enough time and space to fully contact the mixture, adhere enough graphene mixture, and form a fireproof inner layer with moderate thickness. The thickness of the fireproof inner layer can be ensured to be uniform by scraping holes, avoiding the effects of excessive thickness or thinness on the performance of the cable, making the cable more stable and reliable in terms of fire prevention and insulation, and facilitating subsequent recycling and reducing production costs. Appropriate temperature and time can fully solidify the graphene mixture and enhance the bonding strength between the fireproof inner layer and the conductive copper wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the method steps in an embodiment of the present invention. DETAILED DESCRIPTION
[0026] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0027] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0028] Please refer to the attached Figure 1The invention discloses a method for preparing a high temperature resistant fireproof cable, comprising a conductive copper wire, a fireproof inner layer wrapped by the outer wall of the conductive copper wire, an insulating material, and a polyvinyl chloride outer layer wrapped by the outer wall of the fireproof inner layer, wherein the fireproof inner layer is prepared by weight of expanded graphite, terminal hydroxyl polydimethylsiloxane, quartz powder, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate. The specific steps of the method for preparing a high temperature resistant fireproof cable are as follows:
[0029] S100, grinding the expanded graphite into powder to prepare powdered expanded graphite, and then filtering the powdered expanded graphite with a filter to obtain finished powdered expanded graphite;
[0030] Make the particles of expanded graphite and quartz powder smaller and more uniform, improve the mixing effect and the density of the fireproof inner layer;
[0031] S200, mixing the finished powdered expanded graphite with quartz powder, and stirring them evenly to obtain a graphite quartz powder mixture;
[0032] S300, adding hydroxy-terminated polydimethylsiloxane, a mixture of graphite quartz powder, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate into a reaction kettle, and stirring them evenly to obtain an initial graphite mixture material;
[0033] By adjusting the stirring speed, temperature, pressure and other parameters in the reactor, the full reaction and uniform mixing of the components are promoted, and the performance of the graphoxane mixture is improved;
[0034] S400, transferring the initial graphite mixture material into a vacuum tank, and performing a defoaming treatment on the initial graphite mixture material to obtain a graphite oxane mixture;
[0035] S500, then placing the graphoxane mixture into a coating tank, allowing the conductive copper wire to pass through the graphoxane mixture in the coating tank, so that the outer wall of the conductive copper wire adheres to the graphoxane mixture;
[0036] S600, after the conductive copper wire is adhered to the graphene mixture, removing the excess graphene mixture on the conductive copper wire to obtain a primary treated graphite copper wire, and then placing the primary treated graphite copper wire in an oven to obtain a secondary treated graphite copper wire;
[0037] S700, evenly wrap the insulating material on the secondary treated graphite copper wire to form an insulating layer, and perform quality control on the insulating layer. Finally, evenly wrap the polyvinyl chloride sheath on the outside of the insulating layer of the cable to form a sheath layer, obtain a finished fireproof cable, and perform finished product inspection on the finished fireproof cable.
[0038] Adding high-strength fiber materials or metal wires to the cable structure can improve the mechanical strength and tensile strength of the cable, making it more suitable for complex usage environments.
[0039] In one embodiment of the present invention: In S100, the expanded graphite is placed on a grinding device, and the ambient temperature during grinding is controlled between 20°C and 25°C, and then the expanded graphite is ground, and then the powdered expanded graphite is filtered using a filter screen with a mesh size of 300-350 meshes to remove impurities in the powdered expanded graphite, and the quartz powder is ground using the above method, and the quartz powder is filtered using a filter screen with a mesh size of 300-350 meshes.
[0040] In addition to traditional filter mesh filtration, explore the use of electrostatic adsorption filtration or ultrasonic assisted filtration technology. Electrostatic adsorption filtration can more effectively remove tiny impurities, while ultrasonic assisted filtration can make the powdered expanded graphite pass through the filter more evenly during the filtration process, thereby improving the filtration effect. For the grinding of quartz powder, laser particle size analysis technology can be used to monitor the particle size in real time to ensure that it is highly similar to the mesh size of the finished powdered expanded graphite.
[0041] In one embodiment of the present invention: In S200, the finished powdered expanded graphite and quartz powder are placed in an oven to remove moisture, the oven temperature range is 90°C-110°C, and the drying time is 5 hours-6 hours. Then the finished powdered expanded graphite and quartz powder are taken out, and the finished powdered expanded graphite and quartz powder are placed in a mixing tank according to a weight ratio of 1:2, and the alkalinity environment in the mixing tank is controlled so that the pH value in the mixing tank is between 6 and 8. The mixing tank is started, and the stirring speed of the finished powdered expanded graphite and the quartz powder is 50-100 r / min, and the stirring time is 20min-40min.
[0042] Intermittent stirring, variable speed stirring or circulating stirring are used to further improve the mixing uniformity of the finished powdered expanded graphite and quartz powder.
[0043] In one embodiment of the present invention: in S400, after the initial graphite mixture material is transferred to the interior of the vacuum tank, the vacuum degree of the vacuum tank is adjusted to be between 2000Pa-1400Pa, and the temperature in the vacuum tank is controlled to be between 40°C-45°C, and the working time of the vacuum tank is controlled to be between 50min-60min, and then the initial graphite mixture material is defoamed.
[0044] In one embodiment of the present invention: in S500, after placing the graphoxane mixture into the coating tank, the temperature of the coating tank is controlled between 5°C and 20°C, the humidity is controlled between 40% and 60%, and the effective length of the coating tank is 1m-1.5m, and then the conductive copper wire is inserted into the interior of the graphoxane mixture, and the conductive copper wire is moved in the graphoxane mixture at a speed between 0.25m / s and 0.5m / s, so that the graphoxane mixture adheres to the conductive copper wire.
[0045] A special guide plate or stirring device is provided in the tank to allow the mixture to form a more uniform flow around the conductive copper wire, thereby ensuring that a more uniform and sufficient graphoxane mixture adheres to the copper wire.
[0046] In one embodiment of the present invention: in S600, after the graphoxane mixture is adhered to the conductive copper wire, a mixture scraping plate is installed at one end of the coating tank from which the conductive copper wire is led out, and a scraping hole is opened on the mixture scraping plate, and the conductive copper wire adhered to the graphoxane mixture is passed through the scraping hole of the mixture scraping plate to scrape off excess graphoxane mixture, and the graphoxane mixture retained on the conductive copper wire is specifically controlled by the size of the scraping hole and the radius of the conductive copper wire, and the conductive copper wire adhered to the graphoxane mixture is passed through the middle of the scraping hole.
[0047] The edges of the scraped holes are specially processed, such as rounding or coating with wear-resistant materials, to reduce wear on the conductive copper wire.
[0048] In one embodiment of the present invention: In S600, a collecting box is installed below the mixture scraping hole, and the temperature in the collecting box is maintained at 5°C-20°C, so that the scraped graphoxane mixture remains in the same state as the graphoxane mixture in the coating tank, and then the scraped conductive copper wire is transferred to an oven for curing treatment, the temperature in the oven is controlled between 50°C-80°C, and the working time of the oven is between 100min-500min.
[0049] In one embodiment of the present invention: In S600, an arc heating rack is installed at the upper end of the mixture scraping plate, and the arc heating rack is arranged around the conductive copper wire. The graphoxane mixture on the conductive copper wire is preliminarily cured by the arc heating rack. The heating temperature of the arc heating rack is between 50°C and 60°C. A dripping port is opened at the bottom of the arc heating rack, and the scraped graphoxane mixture enters the collection box through the dripping port.
[0050] Example 1, please refer to the attached Figure 1, placing the expanded graphite on a grinding device, controlling the ambient temperature during grinding at 24°C, then grinding the expanded graphite, filtering the powdered expanded graphite with a filter screen with a mesh number of 325, obtaining the finished powdered expanded graphite, and grinding the quartz powder with the above method, filtering the quartz powder with a filter screen with a mesh number of 300-350, placing the finished powdered expanded graphite and quartz powder in an oven to remove moisture, taking out the finished powdered expanded graphite and quartz powder, and mixing the finished powdered expanded graphite with the quartz powder at a ratio of 1:2 The weight ratio of the finished powdered expanded graphite and the quartz powder is placed in a mixing tank, the pH value in the mixing tank is 7, the stirring speed of the mixed stirring of the finished powdered expanded graphite and the quartz powder is 75r / min, the stirring time is 30min, the temperature in the reactor is controlled at 40°C, and the terminal hydroxyl polydimethylsiloxane, the graphite quartz powder mixture, silicone oil, methyl triethoxysilane, γ-aminopropyl triethoxysilane and dibutyltin dilaurate are placed in the reactor in the order and weight ratio, the weight ratio is 4:3:1.5:1:0.3:0.2, the reactor is started, and the items inside are stirred at a stirring speed of 300r / min, The stirring time is 120 minutes, the initial graphite mixture material is obtained, the initial graphite mixture material is transferred to the inside of the vacuum tank, the vacuum degree of the vacuum tank is adjusted to 1700pa, and the temperature in the vacuum tank is controlled at 42°C, and the working time of the vacuum tank is controlled to be 55 minutes, and then the initial graphite mixture material is defoamed to obtain the graphite oxane mixture, and the graphite oxane mixture is placed in the coating tank, the temperature of the coating tank is controlled to be 12°C, and the humidity is 50%, and the conductive copper wire is inserted into the inside of the graphite oxane mixture, and the moving speed of the conductive copper wire in the graphite oxane mixture is 0.The graphite mixture is adhered to the outer wall of the conductive copper wire at a speed of 35 m / s, a mixture scraping plate is installed at one end of the conductive copper wire leading out of the coating tank, and a scraping hole is opened on the mixture scraping plate, and the conductive copper wire adhering to the graphite mixture is scraped off excess graphite mixture through the scraping hole of the mixture scraping plate to obtain a once-treated graphite copper wire, an arc heating frame is installed on the upper end of the mixture scraping plate, and the arc heating frame is arranged around the conductive copper wire, and the graphite mixture on the conductive copper wire is preliminarily cured by the arc heating frame, the heating temperature of the arc heating frame is 55° C., and a dripping port is opened below the arc heating frame, and the scraped graphite mixture passes through the scraping hole of the mixture scraping plate. Enter the collection box through the dripping port, and keep the temperature in the collection box at 12℃, so that the scraped graphite mixture remains in the same state as the graphite mixture in the coating tank, and then transfer the scraped conductive copper wire to the oven for curing treatment. The temperature in the oven is controlled at 65℃, and the working time of the oven is 300min. The secondary treated graphite copper wire is obtained, and the insulating material is evenly wrapped on the secondary treated graphite copper wire to form an insulating layer, and the insulating layer is subjected to quality control treatment. Finally, the polyvinyl chloride outer skin is evenly wrapped outside the insulating layer of the cable to form a sheath layer, and the finished fireproof cable is obtained, and the finished fireproof cable is tested as a finished product. .
[0051] Example 2, please refer to the attached Figure 1, placing the expanded graphite on a grinding device, controlling the ambient temperature during grinding at 21°C, then grinding the expanded graphite, filtering the powdered expanded graphite with a filter screen with a mesh number of 310, obtaining the finished powdered expanded graphite, and grinding the quartz powder with the above method, filtering the quartz powder with a filter screen with a mesh number of 300-350, placing the finished powdered expanded graphite and quartz powder in an oven to remove moisture, taking out the finished powdered expanded graphite and quartz powder, and mixing the finished powdered expanded graphite with the quartz powder at a ratio of 1:2 The weight ratio of the finished powdered expanded graphite and the quartz powder is placed in a mixing tank, the pH value in the mixing tank is 6.5, the stirring speed of the finished powdered expanded graphite and the quartz powder is 60r / min, the stirring time is 25min, the temperature in the reactor is controlled at 35°C, and the terminal hydroxyl polydimethylsiloxane, the graphite quartz powder mixture, silicone oil, methyl triethoxysilane, γ-aminopropyl triethoxysilane and dibutyltin dilaurate are placed in the reactor in the order and weight ratio, the weight ratio is 4:3:1.5:1:0.3:0.2, the reactor is started, and the items inside are stirred at a stirring speed of 200r / mi n, the stirring time is 90 minutes, the initial graphite mixture material is obtained, the initial graphite mixture material is transferred to the inside of the vacuum tank, the vacuum degree of the vacuum tank is adjusted to make the vacuum degree of the vacuum tank at 1800pa, and the temperature in the vacuum tank is controlled at 41°C, and the working time of the vacuum tank is controlled to be 52 minutes, and then the initial graphite mixture material is defoamed to obtain the graphite oxane mixture, and the graphite oxane mixture is placed in the coating tank, the temperature of the coating tank is controlled at 8°C, and the humidity is controlled at 35%, and the conductive copper wire is inserted into the inside of the graphite oxane mixture, and the moving speed of the conductive copper wire in the graphite oxane mixture is 0.3m / s, so that the outer wall of the conductive copper wire adheres to the graphite mixture, a mixture scraping plate is installed at one end of the conductive copper wire leading out of the coating tank, and a scraping hole is opened on the mixture scraping plate, and the conductive copper wire adhering to the graphite mixture is scraped off the excess graphite mixture through the scraping hole of the mixture scraping plate to obtain a once-treated graphite copper wire, and an arc heating frame is installed on the upper end of the mixture scraping plate, and the arc heating frame is arranged around the conductive copper wire, and the graphite mixture on the conductive copper wire is preliminarily cured by the arc heating frame, and the heating temperature of the arc heating frame is 53°C, and a dripping port is opened below the arc heating frame, and the scraped graphite mixture passes through the scraping hole of the mixture scraping plate. Enter the collection box through the dripping port, and keep the temperature in the collection box at 8℃, so that the scraped graphite mixture remains in the same state as the graphite mixture in the coating tank, and then transfer the scraped conductive copper wire to the oven for curing treatment. The temperature in the oven is controlled at 60℃, and the working time of the oven is 200min. The secondary treated graphite copper wire is obtained, and the insulating material is evenly wrapped on the secondary treated graphite copper wire to form an insulating layer, and the insulating layer is subjected to quality control treatment. Finally, the polyvinyl chloride outer skin is evenly wrapped outside the insulating layer of the cable to form a sheath layer, and the finished fireproof cable is obtained, and the finished fireproof cable is tested as a finished product. .
[0052] Example 3, please refer to the attached Figure 1, placing the expanded graphite on a grinding device, controlling the ambient temperature during grinding at 24°C, then grinding the expanded graphite, filtering the powdered expanded graphite with a filter screen with a mesh number of 340, obtaining the finished powdered expanded graphite, and grinding the quartz powder with the above method, filtering the quartz powder with a filter screen with a mesh number of 300-350, placing the finished powdered expanded graphite and quartz powder in an oven to remove moisture, taking out the finished powdered expanded graphite and quartz powder, and mixing the finished powdered expanded graphite with the quartz powder at a ratio of 1:2 The weight ratio of the finished powdered expanded graphite and the quartz powder is placed in a mixing tank, the pH value in the mixing tank is 7.5, the stirring speed of the finished powdered expanded graphite and the quartz powder is 90r / min, the stirring time is 35min, the temperature in the reactor is controlled at 45°C, and the terminal hydroxyl polydimethylsiloxane, the graphite quartz powder mixture, silicone oil, methyl triethoxysilane, γ-aminopropyl triethoxysilane and dibutyltin dilaurate are placed in the reactor in the order and weight ratio, the weight ratio is 4:3:1.5:1:0.3:0.2, the reactor is started, and the items inside are stirred at a stirring speed of 400r / mi n, the stirring time is 150min, the initial graphite mixture material is obtained, the initial graphite mixture material is transferred to the inside of the vacuum tank, the vacuum degree of the vacuum tank is adjusted to make the vacuum degree of the vacuum tank at 1500pa, and the temperature in the vacuum tank is controlled at 44°C, the working time of the vacuum tank is 58min, and then the initial graphite mixture material is defoamed to obtain the graphite oxane mixture, the graphite oxane mixture is placed in the coating tank, the temperature of the coating tank is controlled at 18°C, the humidity is controlled at 55%, the conductive copper wire is inserted into the inside of the graphite oxane mixture, and the moving speed of the conductive copper wire in the graphite oxane mixture is 0.The conductive copper wire is subjected to a pre-curing treatment of graphite oxide mixture on the outer wall of the conductive copper wire, and the graphite oxide mixture is subjected to a pre-curing treatment of graphite oxide mixture on the outer wall of the conductive copper wire. The conductive copper wire is subjected to a pre-curing treatment of graphite oxide mixture on the outer wall of the conductive copper wire, and the graphite oxide mixture is subjected to a pre-curing treatment of graphite oxide mixture on the outer wall of the conductive copper wire. The graphite oxide mixture on the conductive copper wire is subjected to a pre-curing treatment of graphite oxide mixture on the outer wall of the conductive copper wire, and the graphite oxide mixture on the conductive copper wire ... Enter the collection box through the dripping port, and keep the temperature in the collection box at 18℃, so that the scraped graphite mixture remains in the same state as the graphite mixture in the coating tank, and then transfer the scraped conductive copper wire to the oven for curing treatment. The temperature in the oven is controlled at 75℃, and the working time of the oven is 450min. The secondary treated graphite copper wire is obtained, and the insulating material is evenly wrapped on the secondary treated graphite copper wire to form an insulating layer, and the insulating layer is subjected to quality control treatment. Finally, the polyvinyl chloride outer skin is evenly wrapped outside the insulating layer of the cable to form a sheath layer, and the finished fireproof cable is obtained, and the finished fireproof cable is tested as a finished product. .
[0053] The quality of the finished fireproof cables prepared in the above three groups of embodiments was tested, and the testing method was as follows:
[0054] Standard test method for non-prolongation of flame of single cable:
[0055] Operation steps: Suspend a section of the single cable under test in a special burner, and make the flame temperature acting on the cable reach a certain value (exceeding the ignition temperature). After maintaining it for several minutes, remove the fire source.
[0056] Evaluation criteria: Observe whether the tested cable can extinguish itself after the fire source is removed to judge the fire resistance of the cable.
[0057] Material oxygen index method:
[0058] Operation steps: Place a certain number of test samples of a certain size into a special container, first fill it with nitrogen, then gradually fill it with oxygen, and ignite it in a prescribed manner to allow the sample in the container to burn smoothly.
[0059] Evaluation criteria: When the oxygen content reaches a certain value, the sample can continue to burn stably. This oxygen content is called the oxygen index of the material.
[0060] Cable penetration hole flame retardancy assessment standard test method:
[0061] Operation steps: In a special heating furnace, the plugging treatment method of the tested cable passing through the furnace wall is heated according to the "time-temperature" change rate specified by the standard temperature curve, and the heating time lasts for 60min-180min.
[0062] Evaluation criteria: Observe whether the cable section outside the furnace is non-flammable or remains intact.
[0063] Standard test method for flame resistance of bunched cables:
[0064] Operation steps: The principle is basically the same as the standard test method for non-flammability of a single cable. Multiple cables are placed in a bundle and subjected to a combustion test.
[0065] Evaluation criteria: The flame resistance and fireproof performance of the cables are comprehensively evaluated by observing the flame spread, burning time, degree of damage after burning and other indicators of the bundled cables during combustion.
[0066] Fire resistance test:
[0067] Operation steps: According to specific standards and test methods, expose the cable to a high temperature environment to simulate the situation when a fire occurs. After a period of time, check whether the cable can still maintain its function, such as whether it can transmit power or signals normally.
[0068] Evaluation criteria: If the cable can still maintain its basic functions after a certain period of time in a high temperature environment, it means that it has good fire resistance and fire protection performance.
[0069] Embodiment 1
[0070] Can it extinguish itself: Yes;
[0071] Oxygen index of materials: 32%;
[0072] Fire resistance of cable: about 750℃;
[0073] Time to maintain its basic functions: 32 minutes.
[0074] Embodiment 2
[0075] Can it extinguish itself: Yes;
[0076] Oxygen index of materials: 29%;
[0077] Fire resistance of cable: about 740℃;
[0078] Time to maintain its basic functions: 29 minutes.
[0079] Embodiment 3
[0080] Can it extinguish itself: Yes;
[0081] Oxygen index of materials: 34%;
[0082] Fire resistance of cable: about 755℃;
[0083] Time to maintain its basic functions: 34 minutes.
[0084] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a high temperature resistant fireproof cable, comprising a conductive copper wire, a fireproof inner layer wrapped by the outer wall of the conductive copper wire, an insulating material, and a polyvinyl chloride outer layer wrapped by the outer wall of the fireproof inner layer, characterized in that: The fireproof inner layer is prepared by weight of expanded graphite, hydroxyl-terminated polydimethylsiloxane, quartz powder, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate. The specific steps of the preparation method of the high temperature resistant fireproof cable are as follows; S100, grinding the expanded graphite into powder to prepare powdered expanded graphite, and then filtering the powdered expanded graphite with a filter to obtain finished powdered expanded graphite; S200, mixing the finished powdered expanded graphite with quartz powder, and stirring them evenly to obtain a graphite quartz powder mixture; S300, adding hydroxy-terminated polydimethylsiloxane, a mixture of graphite quartz powder, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate into a reaction kettle, and stirring them evenly to obtain an initial graphite mixture material; S400, transferring the initial graphite mixture material into a vacuum tank, and performing a defoaming treatment on the initial graphite mixture material to obtain a graphite oxane mixture; S500, then placing the graphoxane mixture into a coating tank, allowing the conductive copper wire to pass through the graphoxane mixture in the coating tank, so that the outer wall of the conductive copper wire adheres to the graphoxane mixture; S600, after the conductive copper wire is adhered to the graphene mixture, removing the excess graphene mixture on the conductive copper wire to obtain a primary treated graphite copper wire, and then placing the primary treated graphite copper wire in an oven to obtain a secondary treated graphite copper wire; S700, evenly wrap the insulating material on the secondary treated graphite copper wire to form an insulating layer, and perform quality control on the insulating layer. Finally, evenly wrap the polyvinyl chloride sheath on the outside of the insulating layer of the cable to form a sheath layer, obtain a finished fireproof cable, and perform finished product inspection on the finished fireproof cable.
2. The method for preparing a high temperature resistant and fireproof cable according to claim 1, characterized in that: In the S100, the expanded graphite is placed on a grinding device, and the ambient temperature during grinding is controlled between 20° C. and 25° C., and then the expanded graphite is ground, and then the powdered expanded graphite is filtered using a filter screen with a mesh size of 300-350 meshes, so as to remove impurities in the powdered expanded graphite, and the quartz powder is ground using the above method, and the quartz powder is filtered using a filter screen with a mesh size of 300-350 meshes.
3. The method for preparing a high temperature resistant and fireproof cable according to claim 1, characterized in that: In the S200, the finished powdered expanded graphite and quartz powder are placed in an oven to remove moisture, the oven temperature range is 90°C-110°C, and the drying time is 5 hours-6 hours. Then the finished powdered expanded graphite and quartz powder are taken out, and the finished powdered expanded graphite and quartz powder are placed in a mixing tank according to a weight ratio of 1:2, and the alkalinity environment in the mixing tank is controlled so that the pH value in the mixing tank is between 6 and 8. The mixing tank is started, and the stirring speed of the finished powdered expanded graphite and the quartz powder is mixed and stirred at 50-100 r / min, and the stirring time is 20min-40min.
4. The method for preparing a high temperature resistant and fireproof cable according to claim 1, characterized in that: In the S300, the temperature in the reactor is controlled between 30°C and 50°C, and terminal hydroxyl polydimethylsiloxane, a graphite quartz powder mixture, silicone oil, methyltriethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate are placed in the reactor in order and weight ratio, with a weight ratio of 4:3:1.5:1:0.3:0.
2. The reactor is started and the items inside are stirred at a stirring speed of 100-500r / min and a stirring time of 60min-180min.
5. The method for preparing a high temperature resistant and fireproof cable according to claim 1, characterized in that: In the S400, after the initial graphite mixture material is transferred to the interior of the vacuum tank, the vacuum degree of the vacuum tank is adjusted to be between 2000Pa-1400Pa, and the temperature in the vacuum tank is controlled to be between 40°C-45°C, and the working time of the vacuum tank is controlled to be between 50min-60min, and then the initial graphite mixture material is defoamed.
6. The method for preparing a high temperature resistant and fireproof cable according to claim 1, characterized in that: In the S500, after the graphoxane mixture is placed inside the coating tank, the temperature of the coating tank is controlled between 5°C and 20°C, the humidity is controlled between 40% and 60%, and the effective length of the coating tank is 1m-1.5m. Then, the conductive copper wire is inserted into the graphoxane mixture, and the conductive copper wire is moved inside the graphoxane mixture at a speed between 0.25m / s and 0.5m / s, so that the graphoxane mixture adheres to the conductive copper wire.
7. The method for preparing a high temperature resistant and fireproof cable according to claim 1, characterized in that: In the S600, after the conductive copper wire adheres to the graphoxane mixture, a mixture scraping plate is installed at one end of the coating tank from which the conductive copper wire is led out, and a scraping hole is opened on the mixture scraping plate. The conductive copper wire adhered to the graphoxane mixture is passed through the scraping hole of the mixture scraping plate to scrape off excess graphoxane mixture. Specifically, the graphoxane mixture retained on the conductive copper wire is controlled by the size of the scraping hole and the radius of the conductive copper wire, and the conductive copper wire adhered to the graphoxane mixture is passed through the middle of the scraping hole.
8. The method for preparing a high temperature resistant and fireproof cable according to claim 7, characterized in that: In the S600, a collecting box is installed below the mixture scraping hole, and the temperature in the collecting box is maintained between 5°C and 20°C, so that the scraped graphoxane mixture remains in the same state as the graphoxane mixture in the coating tank, and then the scraped conductive copper wire is transferred to an oven for curing treatment. The temperature in the oven is controlled between 50°C and 80°C, and the working time of the oven is between 100min and 500min.
9. The method for preparing a high temperature resistant and fireproof cable according to claim 8, characterized in that: In the S600, an arc heating rack is installed at the upper end of the mixture scraping plate, and the arc heating rack is arranged around the conductive copper wire. The graphoxane mixture on the conductive copper wire is initially cured by the arc heating rack. The heating temperature of the arc heating rack is between 50° C. and 60° C. A dripping port is provided below the arc heating rack, and the scraped graphoxane mixture enters the collection box through the dripping port.
Citation Information
Patent Citations
Expansion flame-proof organosilicon fluid sealant and method of producing the same
CN101368080A
Silicon-based ultrathin fireproof coating material and preparation method thereof
CN110564295A